Arkaismi, konteksti ja kirjuri : sananloppuisen k:n merkintä Christfrid Gananderin kansanrunokokoelmassa - Palola, Elina (Acta Universitatis Ouluensis, 2009)
Archaism, context, and the scrivener. The marking of the word-final k in Christfrid Ganander's collection of old traditional poems.
Keywords: Ganander, Christfrid, : 1741-1790; filologia; folkloristiikka; kansanrunot; kielihistoria; kielitiede; murteet; perinteenkerääjät; suomen kieli; tekstikritiikki; filologi; folkloristik; folkdikter; språkhistoria; språkvetenskap; dialekter; traditionsinsamlare; finska; textkritik; sananloppuinen k